Mediating effect of technology adoption: agricultural extension services enhances sustainability of smallholder tea farmers in Sri Lanka - Kumara, Ahangama Liyanage Rohitha Udaya; Nik Ahmad Sufian Burhan,; Mohamad Fazli Sabri,; Wan Munira Wan Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examined the role of agricultural extension services in promoting sustainability among smallholder tea farms in Sri Lanka through technology adoption. Using the Innovation Diffusion Theory (IDT) and Theory of Planned Behaviour (TPB), it explored how extension services influenced farmers' technology adoption and sustainability practices. Data were collected from 452 smallholder tea farmers in Kandy and Badulla districts using a structured questionnaire. The analysis, conducted via PLS-SEM, revealed that extension services significantly enhanced technology adoption, positively impacting farm sustainability. Findings confirmed that technology adoption mediated the relationship between extension services and sustainability, improving productivity, environmental practices, and social outcomes. The study emphasized a comprehensive sustainability approach integrating extension services, social factors, and economic support. Key recommendations included increasing investment in extension services, addressing financial constraints, and expanding training and resource access. Policymakers and practitioners should strategically support technology adoption initiatives to enhance sustainability in Sri Lanka’s smallholder tea sector. Focused extension programs and novel approaches, such as farmer organizations and farmer field schools, should be developed to promote sustainable tea technologies. Strengthening extension services is crucial for the sector’s long-term viability. Investments in extension services, educational campaigns, and financial support systems will encourage technology adoption, leading to increased productivity, higher incomes, and sustainable growth for smallholder tea farmers in Sri Lanka.